2019
DOI: 10.1111/jcpp.13062
|View full text |Cite
|
Sign up to set email alerts
|

Heritability, stability, and prevalence of tonic and phasic irritability as indicators of disruptive mood dysregulation disorder

Abstract: Background Little is known about genetic and environmental influences on the components of disruptive mood dysregulation disorder (DMDD), tonic irritability (i.e., irritable mood) and phasic irritability (i.e., temper outbursts). This study examined prevalence, stability, and heritability of tonic irritability, phasic irritability, and a DMDD proxy (pDMDD) based on DSM‐5 criteria. Methods pDMDD was derived using data from clinical interviews of parents and their twins (N = 1,431 twin pairs), ages 8–17, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 55 publications
1
23
0
2
Order By: Relevance
“…Finally, the present study did not examine the factors that contribute to the development of tonic and phasic irritability. Consistent with Hawes et al (2019) and Moore et al (2019), our findings suggest that tonic and phasic irritability may have somewhat different etiologies. Hence, future research should extend these findings by examining genetic, environmental, and pathophysiological influences on these dimensions.…”
Section: Strengths and Limitationssupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, the present study did not examine the factors that contribute to the development of tonic and phasic irritability. Consistent with Hawes et al (2019) and Moore et al (2019), our findings suggest that tonic and phasic irritability may have somewhat different etiologies. Hence, future research should extend these findings by examining genetic, environmental, and pathophysiological influences on these dimensions.…”
Section: Strengths and Limitationssupporting
confidence: 84%
“…The two components were highly correlated, and after applying thresholds to account for differences in the prevalence of phasic and tonic irritability, they predicted similar outcomes. Moore and colleagues (Moore et al, 2019) examined the prevalence, stability, and heritability of tonic irritability, phasic irritability, and a DMDD proxy based on DSM-5 criteria in a sample of 8-to 17-year-old twins. They reported that, compared to tonic irritability, phasic irritability was slightly more stable and heritable, and was a stronger indicator of the DMDD latent factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies support developmentally dynamic genetic effects on core features of the disorder, such as irritability, with genetic influences being higher in the female gender and as compared to environmental features [31]. However, the environment is still believed to exert a modulatory effect [32]. Consistently, evidence from gene-by-environment-interaction studies suggests that genetic variation in the hypothalamic-pituitary-adrenal (HPA) axis may interact with the effect of chronic stress in increasing the risk of presenting with a negative affect [33].…”
Section: Discussionmentioning
confidence: 96%
“…Ätiologische Modelle messen -neben personalen Faktoren wie Temperament und neuropsychologischenBesonderheiten -sozialen Faktoren eine besondere Bedeutung bei der Entstehung affektiver Dysregulation bei [22]. In der Interaktion mit Eltern, Gleichaltrigen und Erwachsenen außerhalb der Familie er-werbenKinderEmotionsregulationsstrategien und erproben diese Strategien im Hinblick auf die Erreichung individueller Ziele.…”
Section: Externale Störungen Und Affektive Dysregulationunclassified